The Use of Springs by PDAM for Regional Water Supply in Ungaran, Semarang District - Priyana, Yuli; Sigit, Agus Anggoro (Forum Geografi, 2002)
The study was carried out in Ungaran. The goals of this study are to know and to evaluate the potential spring to add drinking water of Ungaran population. This study uses observation and secondary data analysis. The collected data are meteorology data, the water production of Municipal waterworks, the quality and the quantity of springs, the number of population and the customers. The result of the study shows that there are eight springs with the total debit 157 liter/ second or 6739 m3/ day. The Municipal Waterworks uses 65 liter/ second or 5616 m3/ day with the leaking rate 7% or 5222,88 m3/ day and the rest is used for irrigation. The quality of spring is qualified for drinking water requirement. The need of drinking water for per capita of the population is 136.7 liter/ capita/ day. In 2003 the prediction of the number of consumers is about 20.745 persons, so the total need of drinking water is predicted about 2835.8 m3/ day. The total need of drinking water added with the leak water is 3032.36 m3/ day. The Municipal Waterworks fulfils the need of drinking water for the population especially for the consumers of Municipal Waterworks. However, if the number of customers is accounted based on the number of the population in the pipe sope (Â+ 48246 persons), the Municipal Waterworks will not fulfil the need of drinking water for population, therefore it needs to add volume production of drinking water.